Mujeres migrantes, trabajo y empoderamiento: bolivianas en una ciudad de la periferia globalizada - Myriam González; Susana Sassone (Les Cahiers ALHIM)
The high level of feminization in the international migration in major cities, both from the North and the South, challenges us to study gender, labor and migration relationships in middle- sized cities in the context of globalization, from the perspective of the geography of gender. Comodoro Rivadavia, a Patagonian city linked to the global economy through the oil and fishing industries, is growing rapidly as well as it attracts the new flows, especially the Bolivians. It consists of a familiar migration featured by a gender- labor division, with evidences of female empowerment. The agency ability as regards the Bolivian women entry into the market, which shows the differences and the passage from subordination to empowerment positions, is explained in this paper, taking into account their migration paths, analyzed through qualitative techniques. This article deals with, in the first place, the women migration and particularly those of Bolivians, in the Comodoro Rivadavia's migration diversity. Secondly, the three types of women occupation, salaried and precarious as well as workers in fishing industries and in the domestic sector and other merely business entrepreneurs are examined. Finally, the impact of these gender and labor relationships through appropriation of space and everyday mobility within the urban space are questioned in this article.